Fine and ultrafine atmospheric particulate matter at a multi-influenced urban site: Physicochemical characterization, mutagenicity and cytotoxicity. (February 2017) - Landkocz, Yann; Ledoux, Frédéric; André, Véronique; Cazier, Fabrice; Genevray, Paul; Dewaele, Dorothée; Martin, Perrine J.; Lepers, Capucine; Verdin, Anthony; Courcot, Lucie; Boushina, Saâd; Sichel, François; et al.
Abstract: Particulate Matter (PM) air pollution is one of the major concerns for environment and health. Understanding the heterogeneity and complexity of fine and ultrafine PM is a fundamental issue notably for the assessment of PM toxicological effects. The aim of this study was to evaluate mutagenicity and cytotoxicity of a multi-influenced urban site PM, with or without the ultrafine fraction. For this purpose, PM2.5-0.3 (PM with aerodynamic diameter ranging from 0.3 to 2.5 μm) and PM2.5 were collected in Dunkerque, a French coastal industrial city and were extensively characterized for their physico-chemical properties, including inorganic and organic species. In order to identify the possible sources of atmospheric pollution, specific criteria like Carbon Preference Index (CPI) and PAH characteristic ratios were investigated. Mutagenicity assays using Ames test with TA98, TA102 and YG1041 Salmonella strains with or without S9 activation were performed on native PM sample and PM organic extracts and water-soluble fractions. BEAS-2B cell viability and cell proliferation were evaluated measuring lactate dehydrogenase release and mitochondrial dehydrogenase activity after exposure to PM and their extracts. Several contributing sources were identified in PM: soil resuspension, marine emissions including sea-salt or shipping, road traffic and industrial activities, mainly related to steelmaking or petro-chemistry. Mutagenicity of PM was evidenced, especially for PM2.5, including ultrafine fraction, in relation to PAHs content and possibly nitro-aromatics compounds. PM induced cytotoxic effects at relatively high doses, while alteration of proliferation with low PM doses could be related to underlying mechanisms such as genotoxicity. Graphical abstract: Highlights: PM2.5 at an urban site influenced by natural sources, road traffic, steelmaking and petrochemical industries. Organic extract of PM2.5-0.3 and PM2.5 revealed mutagenic effects on Ames TA98 and YG1041 strain. Different responses for cytotoxicity and proliferation assays for native PM, organic extract or water-soluble fraction. Key-role of the ultrafine fraction in the mutagenicity and cytotoxicity of PM2.5 . Abstract : PM2.5 in a multi-influenced urban site: cytotoxic and proliferative effects induced by native PM, water-soluble and organic fraction; mutagenicity related to organic fraction.